Riqueza de comunidades bacterianas em dois solos sob o cultivo de três frutíferas na Amazônia Central, Brasil - Pereira, Bianca Galúcio (Instituto Nacional de Pesquisas da Amazônia - INPA, 2010)
Microorganisms genetic diversity provides unique and crucial ecosystem, maintaining performances, thus being a fundamental trophic food chain and biogeochemical cycle components. Modern and more efficient techniques for studying soil microbiota, such as the use of molecular tools, are being employed so as to maximize microbial diversity characterization. Soil samples were collected in two rural properties located at RESEX Uatumã, Balbina road in the ramal Da Morena, in the municipality of Presidente Figueiredo, AM, in dark earth and yellow latosol being used to cultivate three native, Amazonian botanical species, açai – Euterpe precatoria Mart., peach palm – Bactris gasipaes Kunth and cupuassu – Theobroma grandiflorum (Willd. ex Spreng.) Schum. Samples were analyzed through Desnaturant Gradient Gel Electrophoresis technique (DGGE) in order to attain Proteobacteria phylum, communities structure characterization, in Alfa, Beta and Gammaproteobacteria classes. Results showed that cultures of açai, cupuassu and peach palm grown in yellow latosol and Dark Earth contemporary are able to differentiate influence the structures of Alfaproteobacteria communities. The contemporary dark earth environment seems to favor the rich for Beta-proteobacteria groups, when compared to the yellow latosol. Indeed, opposite was observed for the Gammaproteobacteria group leading to an indication of greater wealth for the yellow latosol. Fe, Al and percentage of aluminum saturation (m) were the main abiotic factors that influenced the structure of the studied bacterial communities.
Keywords: Latossolo amarelo; Terra preta de índio; Comunidades bacterianas